THE INFLUENCE OF LEARNING STYLES TOWARD STUDENTS READING ACHIEVEMENT AT SMP QURAN AN NAWAWY MOJOKERTO IN THE ACADEMIC YEAR OF 2020/2021 - Yunita Dwi Wikandari (Universitas Samudra, 2022)
The problem of this research is whether or not there may be any correlation between students’ learning style(s) and reading achievement, also this study aims to find how far the influence of learning style(s) towards students reading achievement. Ex post facto design is used in this research. It took place at SMPQ An Nawawy Mojokerto, where the population consists of 35 nineth-grade students, whereas the sample was selected randomly as the learning style(s) used in this research and gathered 65 students for Audithory and Read/write. There are two data collecting techniques in this research, they are questionnaire which is aimed to classify students learning style(s), and reading test (Descriptive text). Then to analyze the data, the researcher uses t –a test. This research found that the students are classified into four learning styles based on the questionnaire (Audithory and Read/write). Most of them preffered to Audithory while others in Read/write learning style. The study's data analysis showed that H˳ is accepted and Ha is rejected. There is no significant difference in learning styles (Audithory and Read/write) toward the students’ reading comprehension achievment (Descriptive text). It can be identified based on the results of t-test analysis, the t value is smaller than t table (t value ≤ t table) that was 3,46 ≤ 5,07. On the other hand, the Alternative Hypothesis (Ha) was rejected and Null Hypothesis (Ho) was accepted.